Australian Staphylococcus aureus Sepsis Outcome Programme annual report, 2013 - Coombs, Geoffrey; Nimmo, G.; Daley, D.; Le, T.; Pearson, J.; Tan, H.; Robinson, J.; Collignon, P.; McLaws, M.; Turnidge, J. (2014)
From 1 January to 31 December 2013, around Australia 26 institutions around Australia participated in the Australian Staphylococcal Sepsis Outcome Programme (ASSOP). The aim of ASSOP 2013 was to determine the proportion of Staphylococcus aureus bacteraemia (SAB) isolates in Australia that are antimicrobial resistant, (with particular emphasis on susceptibility to methicillin) and to characterise the molecular epidemiology of the isolates. Overall 19.1% of the 2,010 SAB episodes were methicillin resistant, which is significantly higher than that reported in most European countries. Although the SAB 30-day all cause mortality appears to be decreasing in Australia, methicillin-resistant SAB associated mortality remains high (20.1%) and was significantly higher than methicillin-sensitive SAB associated mortality (13%) (P< 0.0001). With the exception of the ß-lactams and erythromycin, antimicrobial resistance in methicillin sensitive S. aureus remains rare. However, in addition to the ß-lactams, approximately 50% of methicillin-resistant S. aureus (MRSA) were resistant to erythromycin and ciprofloxacin and approximately 20% were resistant to co-trimoxazole, tetracycline and gentamicin. Linezolid, daptomycin and teicoplanin resistance was detected in a small number of S. aureus isolates. Resistance to vancomycin was not detected. Resistance was largely attributable to 2 healthcare associated MRSA clones; ST22-IV [2B] (EMRSA-15) and ST239-III [3A] (Aus-2/3 EMRSA). ST22-IV [2B] (EMRSA-15) has now become the predominant healthcare associated clone in Australia. Approximately 60% of methicillin-resistant SAB were due to community associated clones. Although polyclonal, almost 50% of community associated clones were characterised as ST93-IV [2B] (Queensland CA-MRSA) and ST1-IV [2B] (WA1). CA-MRSA, in particular the ST45-V [5C2&5] (WA84) clone, has acquired multiple antimicrobial resistance determinants including ciprofloxacin, erythromycin, clindamycin, gentamicin and tetracycline. As CA-MRSA is well established in the Australian community, it is important antimicrobial resistance patterns in community and healthcare associated SAB is monitored as this information will guide therapeutic practices in treating S. aureus sepsis.